OP0023 Four-year imaging outcomes in axial spondyloarthritis patients treated with certolizumab pegol, including patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis. (15th June 2017) - Heijde, D van der; Baraliakos, X; Hermann, KG; Landewé, R; Machado, PM; Maksymowych, W; Davies, O; Peyrecave, N de; Hoepken, B; Bauer, L; Nurminen, T; Braun, J
Abstract : Background: RAPID-axSpA (NCT01087762 ) was a long-term study in patients (pts) with axial spondyloarthritis (axSpA) treated with certolizumab pegol (CZP). This is the first report of 4-year imaging results in CZP-treated axSpA pts, including ankylosing spondylitis (AS) and non-radiographic (nr-)axSpA. Objectives: To report 4-year X-ray and MRI data in CZP-treated axSpA pts. Methods: RAPID-axSpA 1 was double-blind and placebo (PBO)-controlled to Wk24, dose-blind to Wk48, and open-label to Wk204. Pts fulfilling ASAS axSpA criteria were stratified using a local read according to presence/absence of radiographic sacroiliitis (AS/nr-axSpA) at randomization and had active disease. Wk0 CZP-randomized pts (200mg Q2W/400mg Q4W) continued assigned dose; PBO pts received CZP after Wk16/24. Centrally-read lateral X-rays of cervical/lumbar spine at baseline (BL), Wk96, and Wk204 were assessed using the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). Sacroiliac (SI) joint X-rays were scored for sacroiliitis at BL and Wk204. MRI scans performed at BL, Wks12, 48, 96, and 204 were assessed using Spondyloarthritis Research Consortium of Canada (SPARCC) score for SI joints and Berlin score for spine. Data are shown for CZP-treated pts including those starting on PBO. SI joint X-rays (recorded at BL and Wk204) and magnetic resonance imaging (MRI) observed data are presented for pts with valid assessments. mSASSS data were estimated for all pts using observed data and by mixed model for repeated measures (MMRM) analysis. Results: Of 315 CZP-treated pts, 196 had available spinal X-rays and were included in MMRM analyses (BL mean mSASSS: 9.47). 158 pts had MRI assessments (BL mean SPARCC: 8.17 [n=151]; Berlin score: 6.10 [n=153]) and 137 pts had SI joint X-rays at BL and Wk204 (BL: 67.9% radiographic sacroiliitis). In AS pts, mean mSASSS change between BL and Wk204 was 0.98; 0.67 from BL to Wk96, and 0.31 from Wk96 to Wk204 (0.06, -0.01, and 0.07 respectively for nr-axSpA) (Table A). MMRM estimates were similar to observed values (0.62 and 0.70, respectively [axSpA Wk204 mean change]). Limited changes in SI joint X-ray grading were observed to Wk204: only 4.5% of pts progressed to AS, whilst 4.3% moved from an AS classification to nr-axSpA. MRI assessments showed sustained improvement (Table B). Conclusions: This is the first trial to report imaging data in both AS and nr-axSpA pts over 4 years. Limited spinal radiographic progression was observed in CZP-treated pts with lower progression between Wks96 and 204 compared with the first 96 wks. Limited change in radiographic sacroiliitis was observed. Early reductions in MRI inflammation were maintained to Wk204. References: Landewé R. Ann Rheum Dis 2014;73:39–47. Acknowledgements: This study was funded by UCB Pharma. We thank the patients and their caregivers in addition to the investigators and their teams who contributed to this study. Editorial services were provided by Costello Medical Consulting. Disclosure of Interest: D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, UCB Pharma, Employee of: Director of Imaging Rheumatology BV, X. Baraliakos Grant/research support from: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Chugai, Janssen, MSD, Novartis, Pfizer, UCB Pharma, Consultant for: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Chugai, Janssen, MSD, Novartis, Pfizer, UCB Pharma, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Chugai, Janssen, MSD, Novartis, Pfizer, UCB Pharma, K. G. Hermann Speakers bureau: AbbVie, MSD, Pfizer, UCB Pharma, R. Landewé Grant/research support from: Abbott, Amgen, Centocor, Novartis, Pfizer, Roche, Schering-Plough, UCB Pharma, Wyeth, Consultant for: Abbott, Ablynx, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Centocor, GlaxoSmithKline, Novartis, Merck, Pfizer, Roche, Schering-Plough, UCB Pharma, Wyeth, Speakers bureau: Abbott, Amgen, Bristol-Myers Squibb, Centocor, Merck, Pfizer, Roche, Schering-Plough, UCB Pharma, Wyeth, P. Machado Consultant for: AbbVie, Centocor, Janssen, MSD, Novartis, Pfizer, Speakers bureau: AbbVie, Centocor, Janssen, MSD, Novartis, Pfizer, W. Maksymowych Grant/research support from: AbbVie, Amgen, Eli-Lilly, Janssen, Merck, Pfizer, Synarc, Sanofi, UCB Pharma, Consultant for: AbbVie, Amgen, Eli-Lilly, Janssen, Merck, Pfizer, Synarc, Sanofi, UCB Pharma, Speakers bureau: AbbVie, Amgen, Eli-Lilly, Janssen, Merck, Pfizer, Synarc, Sanofi, UCB Pharma, O. Davies Shareholder of: UCB Pharma, Employee of: UCB Pharma, N. de Peyrecave Employee of: UCB Pharma, B. Hoepken Employee of: UCB Pharma, L. Bauer Shareholder of: UCB Pharma, Employee of: UCB Pharma, T. Nurminen Employee of: UCB Pharma, J. Braun Grant/research support from: Abbott, Bristol-Myers Squibb, Celgene, Celltrion, Chugai, Johnson & Johnson, MSD, Novartis, Pfizer, Roche, UCB Pharma, Consultant for: Abbott, Bristol-Myers Squibb, Celgene, Celltrion, Chugai, Johnson & Johnson, MSD, Novartis, Pfizer, Roche, UCB Pharma